Coconut Shell Activated Carbon as a Sustainable Adsorbent for Gold Recovery from Aqueous Leaching Solutions: A Review - Heri Heriyanto; Nufus Kanani; Hendrini Pujiastuti; Rusdi Rusdi (World Chemical Engineering Journal, 2026)
Gold recovery from dilute hydrometallurgical process liquors has become a strategic priority within circular-economy resource management and responsible precious-metal stewardship. Activated carbon dominates gold capture in industrial circuits, particularly in alkaline cyanide systems where the anionic dicyanoaurate complex, Au(CN)₂⁻, is the principal dissolved species; however, economic constraints and sustainability pressures have stimulated growing interest in biomass-derived alternatives. This review critically synthesizes the evidence base for coconut shell activated carbon as a sustainable, high-performance adsorbent for gold recovery from aqueous leaching media, encompassing feedstock selection, activation pathways, pore architecture, adsorption mechanisms, solution speciation in cyanide and cyanide-free systems, and kinetic and equilibrium modelling. The literature demonstrates that gold removal efficiencies of 87–89% are attainable under optimized cyanide-leachate conditions — alkaline pH, gentle agitation, 1.25 g/L adsorbent dose, and approximately 3 h contact — compatible with real processing environments. Feedstock maturity and activation protocol decisively govern adsorption rate, loading capacity, and mechanical integrity, confirming that material quality must be actively engineered. Equilibrium behaviour conforms to the Freundlich isotherm, reflecting energetically heterogeneous surface sites, while kinetics follow pseudo-first-order dynamics with intraparticle diffusion as a co-limiting resistance. Coconut shell activated carbon holds genuine promise as a low-cost, environmentally responsible adsorbent, contingent on deliberate optimization of pore structure, surface chemistry, elution efficiency, regeneration durability, and real-leachate selectivity.